PERAN CUSTOMER SATISFACTION MEMEDIASI PENGARUH INOVASI PRODUK TERHADAP LOYALITAS PELANGGAN TUPPERWARE DI KOTA DENPASAR - Wayan Ariani, Ni; Agung Widagda, I Gst Ngurah Jaya (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.10.TAHUN.2024, 2024)
Currently, the business world is experiencing rapid development and intense competition, Tupperware products have experienced a decline in their market share percentage over the last 5 years. This research aims to explain the role of customer satisfaction in mediating the influence of product innovation on customer loyalty. This research was conducted on Tupperware customers who live in Denpasar City. The sample size used was 110 respondents, using a non-probability sampling method with purposive sampling technique. Data collection uses a questionnaire distributed online via a Google Form link. The data analysis techniques used in this research are descriptive analysis, inferential analysis and VAF test. The results of this research show that product innovation has a positive and significant effect on customer loyalty, product innovation has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on customer loyalty, and customer satisfaction partially mediates the effect of product innovation on Tupperware customer loyalty in the city Denpasar. The implication of this research is to enrich empirical evidence regarding the role of customer satisfaction in mediating the influence of product innovation on Tupperware customer loyalty in Denpasar City and can be used as material for future evaluation for Tupperware.